A double-blind randomized comparative study of triamcinolone hexacetonide and dexamethasone intra-articular injection for the treatment of knee joint arthritis in rheumatoid arthritis. Issue 12 (December 2016) - Hajialilo, Mehrzad; Ghorbanihaghjo, Amir; Valaee, Leyla; Kolahi, Sousan; Rashtchizadeh, Naderh; Amirkhiz, Maryam; Malekmahdavi, Ida; Khabbazi, Alireza
Abstract Intra-articular glucocorticoid (GC) injection has been used for more than half a century in the treatment of refractory synovitis in patients with rheumatoid arthritis (RA). There are limited data about the efficacy of intra-articular injection of various preparations of GCs on inflamed joint. The aim of this study was to compare the efficacy and side effects of intra-articular injection of dexamethasone (DEX) and triamcinolone hexacetonide (TH) in the treatment of knee joint arthritis in RA. In a double-blind randomized clinical trial, 70 patients with RA and knee joint arthritis were recruited to the study. Swelled knee joints were injected with 40 mg TH or 8 mg DEX randomly. The primary outcome measures were reduction of knee joint swelling and pain 1 and 3 weeks after joint injection. The secondary outcome measures were relapse of knee arthritis at 2, 4, and 6 months after injection and side effects of intra-articular injection. Difference in the knee circumferences between DEX and TH groups at weeks 1 and 3 was not significant. The average times of pain reduction after injection were 3.4 ± 2.3 and 2.3 ± 1.8 days in TH and DEX, respectively. There were no differences of knee pain between the two groups. Relapse of knee arthritis was occurred in two (6.7 %) and three (9.4 %) patients in the DEX and TH groups, respectively. Intra-articular injection of DEX like TH causes rapid and long-term reduction of knee pain and swelling in patients with RA and is safe.